2008
DOI: 10.1258/ijsa.2007.007199
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic urethral infection in male sexually transmitted disease clinic attendees

Abstract: The purpose of this study is to determine the prevalence of asymptomatic male patients with urethral infections attending a government sexually transmitted infection clinic in Hong Kong and their microbiological profile. A total of 274 consecutive male patients without any symptoms for urethral infections were recruited. A questionnaire was used to record the symptoms, sexual history and demographics. Further assessment, including urethral smear for Gram stain, gonococcal culture and polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…This statement is also applicable to asymptomatic patients, when the study of urethritis is indicated, by previous studies demonstrating the presence of urethritis-producing microorganisms in the patient 21. It is, however, necessary to conduct further research to clarify the significance of the isolation of microorganisms whose role in the production of urethritis remains unclear.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This statement is also applicable to asymptomatic patients, when the study of urethritis is indicated, by previous studies demonstrating the presence of urethritis-producing microorganisms in the patient 21. It is, however, necessary to conduct further research to clarify the significance of the isolation of microorganisms whose role in the production of urethritis remains unclear.…”
Section: Discussionmentioning
confidence: 94%
“…In Hong Kong, Yu et al ,21 in a study of prevalence of urethral infection in 274 asymptomatic male patients, found 36 patients with NGU and two positive gonococcal cultures. Among the cases of NGU, 17%, 23% and 14% were positive PCR for Chlamydia trachomatis , Mycoplasma genitalium and Ureaplasma urealyticum , respectively, and, further, 14 of the patients positive for Chlamydia trachomatis by PCR had no signs or symptoms of NGU, demonstrating that urethral infection can be present in a significant number of asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In numerous studies (2,9,14,19 232,234,235) in which microscopy has been the dominant feature in making the diagnosis, M. genitalium has been strongly and almost uniformly associated with acute NGU (Fig. 2).…”
Section: Acute Nongonococcal Urethritismentioning
confidence: 99%
“…Researchers in the US have similarly identified that such risk assessments do not accurately identify asymptomatic STI/HIV infections, and should not be the sole basis of STI/HIV care (Duffus et al, 2009;Markos et al, 2007;Yu et al, 2008). This situation may contribute to the vicious cycle of transmission [see Figure 1] (Mercer et al, 2007;White et al, 2005).…”
Section: Accepted Manuscriptmentioning
confidence: 99%